Experimental and numerical investigation on composite single-lap single-bolt sandwich joints with different geometric parameters. (September 2022) - Li, Mengzhen; Liu, Zhiping; Yan, Renjun; Lu, Jiapeng; Guedes Soares, C.
Abstract: Quasi-static tensile behaviour and failure characteristics of composite single-lap single-bolt sandwich joints with different geometric parameters are investigated experimentally and numerically. A finite element model is also established and a progressive failure analysis is conducted to predict the ultimate loads, ultimate displacements, strain, and failure modes of sandwich bolted joints. The numerical results have a great agreement with the experimental ones. The effect of width-to-hole-diameter ratio W/D, end-distance-to-hole-diameter ratio E/D, slope angles and core thicknesses on the ultimate load and failure modes are also discussed. The results show that to ensure bearing failure modes and satisfactory ultimate loads, the design parameters of the composite sandwich bolted joints need to satisfy E/D ≥ 3 to avoid shear-out and cleavage failure modes, and W/D ≥ 5 to avoid net-tension failure modes. Highlights: Composite single-lap single-bolt sandwich joints with different geometric parameters are investigated experimentally. Quasi-static tensile behaviour and failure characteristics of the joints are studied numerically. Progressive failure analysis is used to predict the ultimate loads, displacements, strains, and failure modes of the joints. The effect of width-to-hole-diameter, end-distance-to-hole-diameter, slope angles and core thicknesses are studied. The joints need to satisfy E/D ≥ 3 to avoid shear-out and cleavage failure, and W/D ≥ 5 to avoid net-tension failure.